1999
DOI: 10.1177/s0038038599000346
|View full text |Cite
|
Sign up to set email alerts
|

`Space - The Final Frontier'

Abstract: For too long the built working environment has been excluded from the analysis of work organisations. Buildings, like other cultural artefacts, encapsulate social and economic priorities and values, and represent prevailing power structures. Work buildings, such as offices and factories, both make possible the organisation of the labour process and also serve as structures of non-verbal communication, providing cues on hierarchy, status and appropriate behaviour. Control over the working environment can be see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
127
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(129 citation statements)
references
References 14 publications
1
127
1
Order By: Relevance
“…A cube of space in the workplace (desk, bench or machine) became synonymous with a unit of labor on the payroll. Tayloristic management practices were applied in, indeed constituted by, Taylorized buildings (Baldry, 1999;Baldry et al, 1998). The term 'office', which had once meant a position or function, increasingly referred to a place.…”
Section: Existing Researchmentioning
confidence: 99%
“…A cube of space in the workplace (desk, bench or machine) became synonymous with a unit of labor on the payroll. Tayloristic management practices were applied in, indeed constituted by, Taylorized buildings (Baldry, 1999;Baldry et al, 1998). The term 'office', which had once meant a position or function, increasingly referred to a place.…”
Section: Existing Researchmentioning
confidence: 99%
“…The first is the idea that rearranging spaces and using them in unconventional ways is itself a form of resistance (Baldry, 1999;Halford and Leonard, 2006). For example, Baldry (1999) recounts an example of workers who did not feel they had the right to adjust the lighting in their office even though the light switch was easily within their reach. Halford and Leonard (2006) remind us that 'spaces are often physical representations of discursive constructions' (p. 663).…”
Section: Discussionmentioning
confidence: 98%
“…Space is comprised of the built environment, but it is also a social construction -a manifestation of power relations -and therefore is frequently contested. It carries symbolic importance as a site of meaning-making and identity construction (Baldry, 1999;Taylor and Spicer, 2007). Lewis (2008) has argued that space exists primarily as a site of performance; that is it is created by the ways in which it is used by the people within it (see also Gregson and Rose, 2000).…”
Section: Gender Work and Spacementioning
confidence: 98%
See 1 more Smart Citation
“…Some work has been done in this direction (Baldry, 1999;Edenius & Yakhlef, 2007;Ford & Harding, 2004;Friedman, 2011;Kornberger & Clegg, 2004;Meusburger, 2009;Taylor & Spicer, 2007;Woodward & Ellison, 2010). A review of the growing literature on space in organization studies found the field fragmented but identified three principal streams, each with interesting contributions and shortcomings (Taylor & Spicer, 2007).…”
Section: Theoretical Frameworkmentioning
confidence: 99%